Gene duplications and genetic redundancy in C. elegans. - Woollard, Alison (WormBook, 2005)
Evolutionary innovation requires genetic raw materials upon which selection can act. The duplication of genes is of fundamental importance in providing such raw materials. Gene duplications are very widespread in C. elegans and appear to arise more frequently than in either Drosophila or yeast. It has been proposed that the rate of duplication of a gene is of the same order of magnitude as the rate of mutation per nucleotide site, emphasising the enormous potential that gene duplication has for generating substrates for evolutionary change. The fate of duplicated genes is discussed. Complete functional redundancy seems unstable in the long term. Most models require that equality amongst duplicated genes must be disrupted if they are to be preserved. There are various ways of achieving inequality, involving either the nonfunctionalization of one copy, or one copy acquiring some novel, beneficial function, or both copies becoming partially compromised so that both copies are required to provide the overall function that was previously provided by the single ancestral gene. Examples of C. elegans gene duplications that appear to have followed each of these pathways are considered.